Upaya Meningkatkan Motivasi Belajar Siswa Melalui Permainan Jala Ikan dalam Pembelajaran PJOK di SDN Betet 3 Kota Kediri - Yoga Pramudya Wardana; M. Akbar Husein Allsabah; Moh. Aan Zainul Arifin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study used a cyclical Classroom Action Research (CAR) method to optimize student motivation in Physical Education, Sports, and Health (PJOK). Twenty-eight third-grade students from SDN Betet 3 participated as subjects. The study was divided into two cycles, each with planning, implementation, observation, and evaluation phases.The results showed that student learning motivation averaged 55.7% in Cycle I, then significantly increased to 73.56% in Cycle II. This 17.86% increase reflects a positive shift in student enthusiasm and interest in learning. The implementation of the